Dermatomyositis: Current Insights into Pathogenesis, Diagnosis, and Dermatologic Management - Helen Anastasya; Cut Putri Hazlianda (International Medical Journal Corp. Ltd, 2026)
INTRODUCTION: Dermatomyositis (DM) is a rare, heterogeneous, systemic autoimmune myopathy characterized by hallmark cutaneous manifestations and, typically, symmetric proximal muscle weakness. It’s clinical significance is profound, extending beyond the skin and muscle to involve systemic complications such as interstitial lung disease (ILD) and a strong association with internal malignancy, both of which confer significant morbidity and mortality. The field is currently undergoing a paradigm shift, moving from a monolithic clinical diagnosis to a